Shoveling fuel for a runaway train : errant economists, shameful spenders, and a plan to stop them all - Czech, Brian, 1960- (University of California Press, 2000)
Americans have been conditioned to appreciate, cheer, and serve economic growth. Brian Czech argues that, while economic growth was a good thing for much of American history, somewhere along the way it turned bad, depleting resources, polluting the environment, and threatening posterity.